Cognitive interviews on the Swedish occupational balance questionnaire - Petra Wagman; Linnea Karlsson; Nina Ekblad; Carita Håkansson (Scandinavian Journal of Occupational Therapy)
Background The Occupational Balance Questionnaire (OBQ11) is a commonly used instrument for measuring self-rated occupational balance. It needs further development, and therefore an additional 11 tentative items have been developed. One aspect of this is studying the interpretations and reasoning of people responding to the items/instrument.Aim The aim of this study was to explore and describe how adults interpret and reason in relation to OBQ11 overall, the individual items in the instrument as well as the new tentative items.Method Cognitive interviews were conducted with eight participants varying in age, gender, living situation, education, native language, and self-reported disability. They were included using a combination of purposive and convenience sampling. The interviews were analysed using a content analysis with an inductive approach.Results The analysis resulted in three main categories: ‘Difficulties understanding the items’ (with two subcategories), ‘Structure of the instrument’ (with four subcategories) and ‘Missed perspectives in the instrument’ (with four subcategories).Conclusions The participants considered the items and the instrument relevant for assessing occupational balance. However, the results also revealed the need for more clarifications and changed item order prior to introducing a potential new version of the instrument.